Çekte başvurma hakkı - Eyilik, İsmail (My University, 2017)
Çalışmamızın konusu, süresi içinde bankaya ibraz edilen çekin bedelini tahsiledemeyen hamilin bedeli tahsil etmesine imkân veren başvurma hakkıdır.

The right to petition for the bearer who could not cash the amount of thecheck presented to the bank before its due date, which is a right that allows him/ her tocash the amount, constitutes the subject of the present work.
Keywords: 6102 sayılı Türk Ticaret Kanunu; application; Çek; Çekte Başvurma Hakkı The Law No. 6102; Kıymetli evrak; registration; registration novelties; registration procedure; Ticaret hukuku; Türkiye